2020
DOI: 10.18488/journal.aefr.2020.1010.1062.1076
|View full text |Cite
|
Sign up to set email alerts
|

Poverty Conditions and Patterns of Consumption: An Engel Function Analysis in East Java and Bali, Indonesia

Abstract: This paper aims to analyze consumption patterns of various household goods. The data used in this study was sourced from results of household surveys in the East Java and Bali Provinces in Indonesia. The analytical model used to evaluate household consumption patterns was the Engel function. Engel's function model maps the level of consumption to household income. In this study, the explanatory variables used include household expenditure levels, household characteristics and household poverty conditions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…This research supports Ullah et al (2020) that there is a positive and significant relationship between microfinance institutions (MFIs) and poverty, and recommended that MFIs should offer training sessions before giving credit because they need entrepreneurial skills, business knowledge, and mentorship. Furthermore, Rasyid et al (2020) found that poor households allocate less of their income to basic health needs such as buying side dishes, vegetables, fruit, and meat. Rasyid et al (2020) also recommend that any government assistance for poor households should be accompanied by education on healthy consumption patterns.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research supports Ullah et al (2020) that there is a positive and significant relationship between microfinance institutions (MFIs) and poverty, and recommended that MFIs should offer training sessions before giving credit because they need entrepreneurial skills, business knowledge, and mentorship. Furthermore, Rasyid et al (2020) found that poor households allocate less of their income to basic health needs such as buying side dishes, vegetables, fruit, and meat. Rasyid et al (2020) also recommend that any government assistance for poor households should be accompanied by education on healthy consumption patterns.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…Furthermore, Rasyid et al (2020) found that poor households allocate less of their income to basic health needs such as buying side dishes, vegetables, fruit, and meat. Rasyid et al (2020) also recommend that any government assistance for poor households should be accompanied by education on healthy consumption patterns.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…In a broader scope, Coady et al [14] conducted a review of the targeting program in several developing countries. Several targeting methods are discussed in detail and indexed to measure targeting performance in several countries (including Indonesia) [15]. Evaluation is carried out not only for the transfer program but also includes subsidy programs and job creation programs.…”
Section: Literature Reviewmentioning
confidence: 99%